Prevenção e Reabilitação de Lesões dos Músculos Isquiotibiais e do Ligamento Cruzado Anterior em Contexto Desportivo - Pedro Gil Guimarães Cardoso (2018)
Due to the seriousness and high incidence rate of hamstring and anterior cruciate ligament injuries, these represent the object of study of this work that had as a methodological resource a literature review. The goal was to display the current knowledge about the prevention and rehabilitation of ACL and hamstrings muscle injuries, looking forward to understand why and when these happen and also what factors potentiate its appearance. Thus, we seek to offer relevant data to elaborate effective prevention and rehabilitation programs and also to highlight the importance of these in the sports field in order to optimize individual athletes' efficiency and therefore the teams' performance. According to the performed study, the strengthening and the increased muscle activation of the gluteus is able to reduce the synergistic dominance of the hamstrings and to limit the knee valgus, leading to a risk reduction in both lesions. In this sphere, the inclusion of multifaceted programs that combine eccentric hamstrings, plyometric exercises, proprioception, muscle strengthening, speed and specific sports skills supported by adequate feedback, seem to induce positive changes in the risk factors for hamstring and ACL injury. However, we should not forget that the programs must always be conducted according to the needs of each athlete. So, more than just making programs for each type of injury, it would be more beneficial to integrate custom programs allied to the players' risk factors.